Immune Response (Serum Globulin) in BALB/c Mice after Hookworm Egg Protein Immunization as the Initial Stage of Developing Laboratory Diagnostics: An In Vivo Approach - Santosa, Budi; Fristiani, Arista Kurnia Budi; Dharmana, Edi; Damayanti, Fitriani Nur; Nugroho, Heru Santoso Wahito (Open Access Macedonian Journal of Medical Sciences, 2022)
BACKGROUND: Hookworm infestation is still high and requires practical laboratory diagnosis with high sensitivity and specificity. Meanwhile, there are several limitations associated with the existing method; hence, a new method is essentially needed. Furthermore, the principle of immunological reactions needs to be developed by identifying the extent of hookworm eggs suspension immune responses. The BALB/c mouse is among the most widely used inbred models used in biomedical research and is particularly utilized in immunology and infectious disease research. AIM: This study aims to determine whether the protein concentration of hookworm eggs stimulates antibodies formation (proteins) in the serum of BALB/c mice. METHODS: This is an experimental study with a post-test only control design approach. Egg protein was isolated by removing the contents using a mini drill to immunize BALB/c mice, while the antibody response was observed by spectrophotometer and agglutination methods. RESULTS: The Chi-square and Post hoc statistical tests showed a significance p ≤ 0.001 indicating a relationship between hookworm egg protein and agglutination results. The higher the antibody level, the more visible the agglutination and vice versa. CONCLUSION: These results are expected to form a basis for developing more practical and efficient diagnostic methods based on antigen-antibody reactions.